Avaliação de artrópodes e produção em genótipos de feijão caupi cultivado em sistema itinerente e em aléias - Cardoso, Sandra Regina de Sousa (2006)
The cowpea (Vigna unguiculata (l) Walp.) is one the most important food crops in the Northeast region of Brazil. It presents low productivity associated mainly with the unfavourable climatic conditions, pests, illnesses and the system crop itinerant. The crop systems alley cropping allows the cultive of the drawn out periods and promotes the increase of the biological diversity being able to reduce the occurrence of pests. The present work, had as objective to verify the occurrence of pests and arthropods predators in genotypes of cowpea cultivated in itinerant agriculture and alley cropping. The experiment was carried through in field conditions, in the dry period, the area of rural settlement, "Tico-tico", in the city of Miranda do Norte, Maranhão, Nordest of Brazil. The experimental parcel was of 25 m² and the useful area of 8m2. The parcels had received fertilization complete from NPK, the form of urea, triple superphosphate and potassium chloride, respectively, at the moment of the plantation. The experimental design was a randomized complete block was casualizados with four repetitions. The results of each system had been evaluated estatisticamente through the analysis of variance and the averages submitted to the test of Tukey to the level of 5% of probability. The averages between the two systems had been submitted to test T to the level of 5% of probability. In relation the arthropods found in the ground, it became comparison also enters the systems through analyses for faunistic indexes. As result of the work, it can be concluded that it did not have difference enters the genotypes for the majority of the evaluated parameters and that the population density of insects plagues is similar in the two systems of culture; Barreiro is the cultivate with better performance for the region, in relation to the productive, nutricional aspect and susceptibility the pests; the culture in alleys favors the occurrence of arthropods predators.